PREDIKSI BAHAYA EROSI PADA PERKEBUNAN KELAPA SAWIT (elaise guineneensis jack) DI PT. AGRO NUSA ABADI DESA MOLINO KECAMATAN PETASIA TIMUR KABUPATEN MOROWALI UTARA - Pandji, Susiyadma Rizkia; Monde, Anthon; Hasanah, Uswah (AGROTEKBIS, 2018)
The purpose of this study is to predict the rate of erosion based on some slope in the village of Molino Petasia Eastern District of North Morowali district. The usefulness of this research can used as a source of information for the government in general and provide information about the amount of erosion potential. The research was conducted in December 2015 and February 2016. This study used directly in the field survey and soil sampling for analysis of materials in laboratorium. Then the results of the analysis processed by using the formula USLE (Universal Soil Loss Equation). The results showed that the rate of erosion that occurred in PT. Agro Nusa Abadi is high, moderate to low. Erosion is highest at an inclination of 3% and 8%, while the erosion rate was at an inclination of 3% on replicates 2 and 3, the slope of 8% on repeat 1 (first) whereas the low level of erosion found on a slope of 1%. Keywords: Erosion Prediction, Palm oil and Slope